Pulmonary vasoreactivity predicts long-term outcome in patients with Eisenmenger syndrome receiving bosentan therapy. Issue 18 (28th July 2010) - D'Alto, Michele; Romeo, Emanuele; Argiento, Paola; Santoro, Giuseppe; Sarubbi, Berardo; Gaio, Giampiero; Mélot, Christian; Russo, Maria Giovanna; Naeije, Robert; Calabrò, Raffaele
Abstract : Background: Vasoreactivity testing is recommended in the management of pulmonary arterial hypertension (PAH), but its clinical relevance in congenital heart disease (CHD)-associated PAH has not been established. Objective: To determine whether residual pulmonary vascular responsiveness to intravenous. epoprostenol is predictive of clinical outcome in patients with CHD-PAH and Eisenmenger syndrome. Methods and results: A diagnostic right heart catheterisation with reversibility testing using epoprostenol infusion was performed in 38 consecutive patients with CHD-PAH and Eisenmenger syndrome. Patients were treated with bosentan and were assessed every 3 months. Clinical worsening was defined as death from any cause, heart–lung or lung transplantation (or on the waiting list for this procedure), hospitalisation for PAH, or symptom exacerbation defined as a ≥20% decrease in the 6 min walking distance on two consecutive tests, an increase in WHO functional class, or worsening right heart failure. The mean follow-up was 33±17 months. Sixteen patients showed clinical worsening. Although they did not differ from the other patients in their baseline exercise capacity, haemodynamic characteristics and underlying CHD, pulmonary vascular resistance index (PVRi) was less reversible (ΔPVRi 29±21 vs 52±14%, p = 0.0003). At univariate analysis, systemic vascular resistance, PVRi and ΔPVRi were significant predictors of clinical worsening. At multivariate Cox proportional hazards regression model, ΔPVRi was found to be the only independent predictor of clinical worsening (HR=0.973, 95% CI 0.95 to 0.99; p = 0.01). ΔPVRi ≥25% had a positive and negative predictive value for clinical worsening of 100% and 75.9%, respectively. Conclusion: Pulmonary vasoreactivity is a significant predictor of clinical worsening in patients with CHD-PAH.